Corneal Dystrophy Adds to the Frustration of a Dry Eye Patient - Zakem, Michelle; Bitton, Etty (Canadian Journal of Optometry, 2017)
PURPOSE This case report highlights how epithelial basement membrane dystrophy (EBMD), coupled with dry eye, can contribute to symptoms of unstable vi-sion and discomfort. This report also reviews corneal dystrophies and offers eye care practitioners (ECPs) clinical pearls for identifying key features. CASE REPORT A 62-year-old Caucasian female presented for a dry eye evaluation due to fluctuating vision and longstanding ocular discomfort, despite ocular lubri-cation. Anterior segment examination revealed Meibomian gland dysfunc-tion (MGD), upper lid margin staining (ULMS) and anterior blepharitis. The patient was unaware of a pre-existing EBMD and this lack of knowl-edge contributed to her frustration concerning her unstable vision, which she had solely attributed to her glasses. Management included warm com-presses for MGD and targeted preservative-free artificial tears for ULMS and EBMD. Photographs were essential for educating the patient with respect to the irregularities of the ocular surface and its effect on vision. This provided a deeper understanding of the multifactorial nature of her symptoms. CONCLUSION Unstable and/or poor vision is among the main reasons why patients con-sult ECPs and it can be difficult to identify contributory factors. This report highlights that additional chair time may be warranted to educate patients on the multifactorial nature of dry eye and the complexities of corneal dys-trophy.